Pengaruh Perilaku Kepemimpinan Dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan - Heru Budi Santoso; Krisna Abhi Padhana; Siti Masfufah (JURNAL MANAJEMEN & ORGANISASI REVIEW (MANOR), 2026)
This study aims to analyze the influence of leadership behavior and work motivation—based on Maslow’s hierarchy of needs on the job performance of employees at the Nalanda Institute in Jakarta. This study employs a quantitative approach with an explanatory design, using a saturated sample, and data collection was conducted through questionnaires, observations, and documentation. The results show that the leadership styles most frequently perceived by Nalanda Institute employees are the democratic style, followed by the laissez-faire style, and the autocratic style. Regarding work performance, the majority of employees fall into the moderate, high, and low categories. The dimensions of work motivation according to Maslow’s hierarchy show a similar pattern, with most employees falling into the moderate category. This study implies that the Nalanda Institute needs to maintain a democratic leadership style and strengthen employee recognition and self-development programs so that work performance can improve sustainably. The findings of this study are expected to contribute to and inform the institution’s efforts to formulate more efficient and effective employee development strategies for the future.